(untitled) (Ukrainian Journal of Ophthalmology, 2023)
Non-combat gunshot wounds are uncommon injuries in the pediatric population of Ukraine. Here, we present a case of gunshot wound of the face, orbit and brain. Early and late features of damage to the eye resulting from a gunshot wound are reviewed.